1988
DOI: 10.1016/0014-5793(88)80215-1
|View full text |Cite
|
Sign up to set email alerts
|

Association of a myristoylated protein with a biological membrane and its increased phosphorylation by protein kinase C

Abstract: A hydrophilic enzyme, lysozyme, was myristoylated in vitro by the N‐hydroxysuccinimide ester of myristic acid, and the monomyristoylated lysozyme was isolated by CM‐cellulose cation‐exchange column chromatography. The monomyristoylated lysozyme associated with phospholipid vesicles, whereas the association of native lysozyme was negligible. The membrane‐associated monomyristoylated lysozyme was phosphorylated with partially purified rat brain Ca2+‐ and phospholipid‐dependent protein kinase (protein kinase C) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…In these mechanisms, plasma membrane binding of FMNL2 mediated by protein N-myristoylation seems to play vital role in the recognition of FMNL2 by the membrane-bound activated form of PKCα. In fact, many studies have shown that N-myristoylation-dependent membrane binding plays critical role in the phosphorylation of substrate proteins by PKC [13,14,39,40].…”
Section: Discussionmentioning
confidence: 99%
“…In these mechanisms, plasma membrane binding of FMNL2 mediated by protein N-myristoylation seems to play vital role in the recognition of FMNL2 by the membrane-bound activated form of PKCα. In fact, many studies have shown that N-myristoylation-dependent membrane binding plays critical role in the phosphorylation of substrate proteins by PKC [13,14,39,40].…”
Section: Discussionmentioning
confidence: 99%
“…6,11) Chemical modifications of proteins with long-chain fatty acids using the N-hydroxysuccinimide ester of fatty acids, 11) and gene fusion of an N-myristoylation signal sequence to the 5 0 -end of the cDNA coding for the target protein, 6) are effective strategies to introduce acyl groups and to immobilize hydrophilic proteins to a liposomal surface. Since liposomes are non-toxic and ideal as drug carriers, and since they are also biodegradable, these approaches may be applicable to drug-delivery systems.…”
Section: Preparation Of N-acylated Proteins Modified With Fatty Acidsmentioning
confidence: 99%
“…If natural non-transmembrane acyl-proteins are difficult to obtain, artificial ones can be prepared either through classical chemical modification of proteins [8][9][10][11] or by using reverse micelles as microreactors (enzymes [12][13][14], antibodies [15] and Fab fragments [16]). The latter structures present the advantage of a finely tunable diameter, since their inner volume is proportional to the water amount present in the system, whereas their surface area depends on the surfactant quantity used.…”
Section: Introductionmentioning
confidence: 99%